2022
DOI: 10.3389/fphys.2022.848508
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory Metabolomics Reveals the Association of the Metabolites With Clinical Features in the Patients With Intrahepatic Cholestasis of Pregnancy

Abstract: Objective: Intrahepatic cholestasis of pregnancy (ICP) is associated with an increased risk of adverse pregnancy to the mother and fetus. As yet, the metabolic profiles and the association of the clinical features remain obscure.Methods: Fifty-seven healthy pregnant women and 52 patients with ICP were recruited in this study. Plasma samples were collected from pregnancies who received prenatal care between 30 and 36 weeks. Untargeted metabolomics to portray the metabolic profiles were performed by LC/MS. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Estrone sulfate and Dehydroepiandrosterone sulfate are two of the most abundant steroids in the human circulation. Liu et al suggested that the estrone sulfate level was relevant to increased BA level [ 31 ]. Previous studies had suggested the positively relationship between BAs efflux transporter in the hepatocytes and Dehydroepiandrosterone sulfate [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estrone sulfate and Dehydroepiandrosterone sulfate are two of the most abundant steroids in the human circulation. Liu et al suggested that the estrone sulfate level was relevant to increased BA level [ 31 ]. Previous studies had suggested the positively relationship between BAs efflux transporter in the hepatocytes and Dehydroepiandrosterone sulfate [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… 69 , 70 In eukaryotic cells, elevated bile acid levels have been implied to be relevant to abnormal tryptophan metabolism, and bacteria that produce branched-chain amino acids such as leucine are known to affect bile hemostasis by conjugating bile acids. 71 , 72 Thus, it can be inferred that an increase in these amino acids is important for the pathogenesis of C. jejuni .…”
Section: Discussionmentioning
confidence: 99%
“…Investigating putative hubs can reveal important genes as, for example, the cold-regulated gene Lolium perenne LIR1 ( LpLIR1 ) (Ciannamea et al 2007) represented by the hub gene coded as 22 in Figure 5, which is located at chr5:155166187-155167265 in the L. perenne genome and appears to act in the photoperiodic regulation of flowering. Another example is hub 7, which represents the PDX1.1 gene, involved in the biosynthesis of vitamin B6 and protection against stresses (Liu et al 2022). Overexpression of PDX proteins was shown to increase seed size and biomass in Arabidopsis (Raschke et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, ℓ 1 -penalization has been one of the main techniques used to make sparse inference in a Gaussian Markov random field (Friedmanet al 2007), yielding a sparse structured precision matrix ∑ −1 which, in turn, can be converted into an undirected network and further analyzed for its topological properties. This approach has been applied to the study of gene expression (Shahdoust et al 2019; Wu et al 2013) and metabolomic (Liu et al 2022) data in humans, with few examples in plants(Li and Jackson 2015; Kapoor et al 2021;e Lima et al 2018; Bartzis et al 2017). With a selected set of candidate features recovered from gene co-expression and metabolic networks, one can perform omic-phenotype integration.…”
Section: Introductionmentioning
confidence: 99%